Bioflavonoids from the leaves of ficus deltoidea jack with a-glucosidase inhibition / Nor Akmal Yati Sulong - Sulong, Nor Akmal Yati (2014)
The leaves of Ficus deltoidea are used as a traditional medicine by diabetes patients in Malaysia. The objective of the study is to identify and evaluate bioactive constituents with in vivo a-glucosidase inhibition. The partitioned extracts, subfractions and pure bioactive constituents were subjected to the in vitro and in vivo a-glucosidase inhibition assay. The identified bioactive constituents were administered orally to sucrose loaded normoglycemic mice and induced diabetic rats. The postprandial blood glucose levels were monitored at 30 min interval. Acute toxicity was evaluated in both normoglycemic mice and induced diabetic rats. Bioactivity guided fractionation led to the isolation of C-glycosyl bioflavonoids namely,vitexin (78) and isovitexin (79). Oral administration of 1 mg/kg of either vitexin or isovitexin significantly (p<0.05) reduced the postprandial blood glucose level in sucrose loaded normoglycemic mice at 30 min. The percentage of postprandial blood glucose reduction was highest in sucrose loaded induced diabetic rats administered orally with 200 mg/kg of vitexin or 100 mg/kg of isovitexin. Both vitexin and isovitexin did not exert any signs of toxicity at the highest dose of 2 g/kg administered orally to normoglycemic mice and induced diabetic rats. Both the C-glycosyl bioflavonoids, namely, vitexin and isovitexin exhibited in vivo a-glucosidase inhibition.